Transormasi Moda Produksi Pengolahan Sagu dan Implikasinya Terhadap Sosial-Ekononi - Arlando P. Risambessy; J. D. Siwalette; J. F. Sopamena (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The role of new modes of production can affect the increase in sago production and affect the production relationship that occurs in Rutong Village, South Leitimur District with a total of 6 respondents. Descriptive research and qualified analysis. The results showed that sago production using semi-modern modes of production can increase more production yields and production relationships where labor is no longer limited to the nuclear family but farmers cooperate with communities that have production modes as a working group.